2018
DOI: 10.1021/acs.inorgchem.7b02474
|View full text |Cite
|
Sign up to set email alerts
|

Drastic Redox Shift and Electronic Structural Changes of a Manganese(III)-Salen Oxidation Catalyst upon Reaction with Hydroxide and Cyanide Ion

Abstract: Flexible redox properties of a metal complex are important for redox catalysis. The present study shows that the reaction of a manganese(III) salen complex, which is a well-known oxidation catalyst, with hydroxide ion gives a transient manganese(III) species with drastically lowered redox potential, where the redox difference is -1.21 V. The reaction with cyanide ion gives a stable manganese(III) species with almost the same spectroscopic and redox properties, which was characterized as an anionic [Mn(salen)(C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…The present study shows a clear correlation between E ox – E red and λ em , as shown in Figure . The E ox of salen complexes comes from the one-electron oxidation of the phenolate moiety, as indicated from the detailed studies on phenoxyl radicals from salen complexes by us and others. The E red of salen complexes bearing redox-inactive metal is assigned as arising from one-electron reduction of the azomethine moiety, which is indeed not redox-innocent. , Then, the most probable photoexcitation pathway is a transition from the phenolate moiety as an electron donor to the azomethine moiety as an electron acceptor, as shown in Figure .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The present study shows a clear correlation between E ox – E red and λ em , as shown in Figure . The E ox of salen complexes comes from the one-electron oxidation of the phenolate moiety, as indicated from the detailed studies on phenoxyl radicals from salen complexes by us and others. The E red of salen complexes bearing redox-inactive metal is assigned as arising from one-electron reduction of the azomethine moiety, which is indeed not redox-innocent. , Then, the most probable photoexcitation pathway is a transition from the phenolate moiety as an electron donor to the azomethine moiety as an electron acceptor, as shown in Figure .…”
Section: Resultsmentioning
confidence: 97%
“… 41 44 The E red of salen complexes bearing redox-inactive metal is assigned as arising from one-electron reduction of the azomethine moiety, which is indeed not redox-innocent. 45 , 46 Then, the most probable photoexcitation pathway is a transition from the phenolate moiety as an electron donor to the azomethine moiety as an electron acceptor, as shown in Figure 13 .…”
Section: Resultsmentioning
confidence: 99%